Une explication cognitive des effets attribués à la c-commande dans les contraintes sur la coréférence - Denis Bouchard (Corela)
The notion of c-command occurs in several constraints on the interpretation of elements which are dependent on others for the interpretation of their reference. However, it is rather surprising that a syntactic relation should constrain referential interpretation : it seems totally accidental, there is no clear motivation for it. That syntactic relation actually corresponds to the signifiant of a combinatorial sign, and if we look at the signifié side of that relation instead of its signifiant, its presence in a constraint on referential dependency follows naturally from semantic/conceptual properties of reference and predication.